Becoming female: Ovarian differentiation from an evolutionary perspective - Nicol, Barbara; Estermann, Martin A.; Yao, Humphrey H-C; Mellouk, Namya (Frontiers in Cell and Developmental Biology, 2022)
Differentiation of the bipotential gonadal primordium into ovaries and testes is a common process among vertebrate species. While vertebrate ovaries eventually share the same functions of producing oocytes and estrogens, ovarian differentiation relies on different morphogenetic, cellular, and molecular cues depending on species. The aim of this review is to highlight the conserved and divergent features of ovarian differentiation through an evolutionary perspective. From teleosts to mammals, each clade or species has a different story to tell. For this purpose, this review focuses on three specific aspects of ovarian differentiation: ovarian morphogenesis, the evolution of the role of estrogens on ovarian differentiation and the molecular pathways involved in granulosa cell determination and maintenance.